2020
DOI: 10.1021/acs.orglett.0c02749
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Amino-2′-hydroxy-1,1′-biaryls via Cascade Benzannulation and C–N Bond Cleavage Sequence

Abstract: A serendipitous synthesis of N-substituted 2-amino-2′-hydroxy-1,1′-biaryls through an aryne annulation with indolyl β-ketonitrile/ester in a cascade manner is demonstrated. The reaction sequence involves benzyne-mediated [2 + 2] Stoltz-type cycloaddition–cleavage and intramolecular Michael addition followed by C–N bond cleavage under transition-metal-free reaction conditions. Interestingly, while [4 + 2] Diels–Alder reaction is a possible pathway, no traces of the regioisomer was isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…As a similar approach, Manna and co‐workers used tosylhydrazones for constructing pyrazoles [6b] . Another C2‐N1 breaking transformation of indoles featuring aryne insertion to afford naphthols was reported by Adepu and Chandrasekhar very recently [6c] . In 2020, Park and coauthors reported that alkynes and ammonium acetate can serve as an indole editing reagent to afford pyridines [6d] .…”
Section: Methodsmentioning
confidence: 98%
“…As a similar approach, Manna and co‐workers used tosylhydrazones for constructing pyrazoles [6b] . Another C2‐N1 breaking transformation of indoles featuring aryne insertion to afford naphthols was reported by Adepu and Chandrasekhar very recently [6c] . In 2020, Park and coauthors reported that alkynes and ammonium acetate can serve as an indole editing reagent to afford pyridines [6d] .…”
Section: Methodsmentioning
confidence: 98%
“…Initially, we investigated the use of PEG as a solvent on our recent cascade of benzannulation reaction. 11 We carried out the cascade benzannulation reaction of N-Boc indole β-ketonitrile 1a with aryne precursor, using PEG-400 as a solvent, without additive at 60 o C and found 3 instead of 4a reported by us as a major product which might be due to the quenching the aryl anion formed after the nucleophilic addition by terminal hydroxy groups of PEG solvent and resulting in the simple arylation reaction (Scheme 1a). To our delight when the same reaction was performed in PEGDME (average molecular weight 240), the annulation product was obtained in 70% yield which showcases the great advantage over a reaction in THF with 18crown-6 (Conditions A and B, Scheme 1b).…”
Section: Scheme 1 Reaction Of Indole β-Ketonitrile With Aryne Precursormentioning
confidence: 91%
“…Compound 1b was synthesized from N-methyl-5-bromoindole according to a previously reported procedure. 11 A solution of cyanoacetic acid (244 mg, 2.87 mmol, 1.2 equiv.) and propionic anhydride (4 mL) was heated to 65 °C using an oil bath for 10 min.…”
Section: -(5-bromo-1-methyl-1h-indol-3-yl)-3-oxopropanenitrile (1b)mentioning
confidence: 99%
See 1 more Smart Citation
“…Domino reactions involving aryne chemistry form another strategy followed for the synthesis of polycyclic organic frameworks. 5,6 Annulation reactions involving aryne α-bond insertion are rarely known, but recently, Wu and co-workers reported the synthesis of substituted naphthalenes by sequential α-bond insertion 7 followed by benzannulation reactions of arynes. 8 We recently reported aromaticity driven access to cycloalkyl fused naphthalenes.…”
mentioning
confidence: 99%